Get the information you need quickly and easily with IDNLearn.com. Join our knowledgeable community to find the answers you need for any topic or issue.

Select the correct answer.

For which system of inequalities is [tex]$(3,-7)$[/tex] a solution?

A.
[tex]\[
\begin{array}{l}
x + y \ \textless \ -4 \\
3x + 2y \ \textless \ -5
\end{array}
\][/tex]

B.
[tex]\[
\begin{array}{l}
x + y \leq -4 \\
3x + 2y \ \textless \ -5
\end{array}
\][/tex]

C.
[tex]\[
\begin{array}{l}
x + y \ \textless \ -4 \\
3x + 2y \leq -5
\end{array}
\][/tex]

D.
[tex]\[
\begin{array}{l}
x + y \leq -4 \\
3x + 2y \leq -5
\end{array}
\][/tex]


Sagot :

To determine for which system of inequalities the point [tex]\((3, -7)\)[/tex] is a solution, we will check each system individually.

First, let's assign the values of the point to the variables [tex]\( x \)[/tex] and [tex]\( y \)[/tex]:
[tex]\[ x = 3 \][/tex]
[tex]\[ y = -7 \][/tex]

Now let's examine each system:

System A:
[tex]\[ \begin{array}{l} x + y < -4 \\ 3x + 2y < -5 \end{array} \][/tex]

Substituting [tex]\( x = 3 \)[/tex] and [tex]\( y = -7 \)[/tex] into the inequalities:
[tex]\[ 3 + (-7) < -4 \][/tex]
[tex]\[ -4 < -4 \quad \text{(False)} \][/tex]
For the second inequality:
[tex]\[ 3(3) + 2(-7) < -5 \][/tex]
[tex]\[ 9 - 14 < -5 \][/tex]
[tex]\[ -5 < -5 \quad \text{(False)} \][/tex]

Since the first inequality is false, [tex]\((3, -7)\)[/tex] is not a solution to System A.

System B:
[tex]\[ \begin{array}{l} x + y \leq -4 \\ 3x + 2y < -5 \end{array} \][/tex]

Substituting [tex]\( x = 3 \)[/tex] and [tex]\( y = -7 \)[/tex] into the inequalities:
[tex]\[ 3 + (-7) \leq -4 \][/tex]
[tex]\[ -4 \leq -4 \quad \text{(True)} \][/tex]
For the second inequality:
[tex]\[ 3(3) + 2(-7) < -5 \][/tex]
[tex]\[ 9 - 14 < -5 \][/tex]
[tex]\[ -5 < -5 \quad \text{(False)} \][/tex]

Since the second inequality is false, [tex]\((3, -7)\)[/tex] is not a solution to System B.

System C:
[tex]\[ \begin{array}{l} x + y < -4 \\ 3x + 2y \leq -5 \end{array} \][/tex]

Substituting [tex]\( x = 3 \)[/tex] and [tex]\( y = -7 \)[/tex] into the inequalities:
[tex]\[ 3 + (-7) < -4 \][/tex]
[tex]\[ -4 < -4 \quad \text{(False)} \][/tex]
For the second inequality:
[tex]\[ 3(3) + 2(-7) \leq -5 \][/tex]
[tex]\[ 9 - 14 \leq -5 \][/tex]
[tex]\[ -5 \leq -5 \quad \text{(True)} \][/tex]

Since the first inequality is false, [tex]\((3, -7)\)[/tex] is not a solution to System C.

System D:
[tex]\[ \begin{array}{l} x + y \leq -4 \\ 3x + 2y \leq -5 \end{array} \][/tex]

Substituting [tex]\( x = 3 \)[/tex] and [tex]\( y = -7 \)[/tex] into the inequalities:
[tex]\[ 3 + (-7) \leq -4 \][/tex]
[tex]\[ -4 \leq -4 \quad \text{(True)} \][/tex]
For the second inequality:
[tex]\[ 3(3) + 2(-7) \leq -5 \][/tex]
[tex]\[ 9 - 14 \leq -5 \][/tex]
[tex]\[ -5 \leq -5 \quad \text{(True)} \][/tex]

Since both inequalities are true, [tex]\((3, -7)\)[/tex] is a solution to System D.

Hence, the correct answer is:
[tex]\[ \boxed{4} \][/tex]